2018
DOI: 10.1007/s10689-018-0093-3
|View full text |Cite
|
Sign up to set email alerts
|

Low-level parental mosaicism in an apparent de novo case of Peutz–Jeghers syndrome

Abstract: We report the case of a female found to have mosaicism for mutation in the STK11 gene, with the mutant allele expressed in her gametes, evident by her affected offspring, and in her gastrointestinal tract demonstrated on an excised polyp analysed for diagnosis. Mosaicism for Peutz-Jeghers syndrome (PJS) has been reported in a small number of cases previously but a clinical presentation such as this has not previously been described. This finding of mosaicism was several years after initial investigations faile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…14 However, in 10%-15% of patients, a PV in STK11 was still not detected. In 2016, the first report of mosaicism for a PV in STK11 was published 15 and this was followed by Butel-Simoes et al 16 and our own case report in 2021. 17 In the present study, we found that 82% of the Danish patients carried a PV that could be detected with Sanger sequencing, while larger CNVs were identified in 13%.…”
Section: Considerations On Geneticsmentioning
confidence: 70%
“…14 However, in 10%-15% of patients, a PV in STK11 was still not detected. In 2016, the first report of mosaicism for a PV in STK11 was published 15 and this was followed by Butel-Simoes et al 16 and our own case report in 2021. 17 In the present study, we found that 82% of the Danish patients carried a PV that could be detected with Sanger sequencing, while larger CNVs were identified in 13%.…”
Section: Considerations On Geneticsmentioning
confidence: 70%
“…Seven PJS patients with somatic chimerism have been identified so far, and polygenic combinations involving STK11 and other target genes may also be considered. 26,27 STK11 and other target genes have a variety of mutation types and loci, most of which are frameshifts or insignificant variations. 11,25,28 At present, effective mutation targets cannot be found from the complex and redundant massive data on gene mutation.…”
Section: Research Progress On Pathogenesis Of Pjsmentioning
confidence: 99%
“…Genetic heterogeneity has been suggested on the basis that PVs are not found in all patients with PJS; however, despite considerable effort, no other gene has been associated with PJS so far [21,30,[41][42][43][44]. Patients without detectable PVs might be explained by variants in non-coding sequences, limitations in technique, misdiagnosis, as well as mosaicism-the latter having been reported in a few case reports [45,46]. Screening for STK11 mosaicism in blood or other tissue could be considered in patients who fulfill clinical criteria for PJS but without a detectable PV by initial genetic screening.…”
Section: Stk11 (Lkb1) (Mim 602216mentioning
confidence: 99%